Прогресивні методи створення ефективного простору для занять екстремальними видами спорту на прикладі скейт-парків - Прокопов, Олександр Васильович; Prokopov, Alexander; Прокопов, Александр Васильевич (КНУБА, 2020)
У статті розглянуто питання недосконалості функціонально - просторової організації існуючих скейт-парків та освітлено рекомендації щодо поліпшення їх функціональності з урахуваннях особливостей субкультури скейтбордистів та основ тематичного парку. The article describes the problem of absence of organizational and elaborated space for extreme sports. The article describes the problem of lack of organizational and spatial thoughtfulness of space for extreme sports. Skateboarding is a free, bold subculture which popularity is growing up around the world every day and is one of the Olympic sports. People, regardless of social status, age, religion or gender, unite into a single subculture of skateboarding. It has its own ideology, traditions, clothing, music, graffiti and a common space for extreme sports. Historically, members of this subculture have preferred the streets - both because of their own desire to express their freedom, and because of the lack of well-organized skate parks. Although it should be considered fair that with the development of skateboarding as a sport, the transition to a specially built skate park is a logical stage of its original evolution. But the skate parks, built without taking into account the wishes of skateboarders, do not cause them much admiration, but only numerous injuries and vandalism in relation to these spaces. Therefore, to improve this situation and strengthen the interest of skateboarders need to consider certain principles of improving the spatial organization of the skate park, including: zoning of the skate park, the maximum use of landscaping, to enable skateboarders to participate in the aesthetic design of the park with graffiti art, to control the space of the skate park with the help of modular elements, choose acceptable places for the location of the skate park, review the organization of hybrid parks and take into account the principles of organization of theme parks.
Progressive methods of creating an effective space for extreme sports on the example of skate parks
Прогрессивные методы создания эффективного пространства для занятий экстремальными видами спорта на примере скейт-парков
Keywords: дизайн скейт-парку; скейтбординг; субкультура; екстремальний спорт; тематичний парк; skate park design; skateboarding; subculture; extreme sports; theme park